“Weaponization” of migrants: crisis at Latvia-Belarus and Poland-Belarus borders. - Skrastiņa, Monta (Riga Graduate School of Law, 2024)
Migration is a phenomenon that has existed for a majority of human history. However, due to changing relations between countries, migration has transformed into an instrument for changing the political landscape. The intentional use of migrants as a coercive tool, also known as "weaponization" of migrants, has emerged as a significant concern for the European Union. Since 2021, Belarus has artificially created a new migratory route from the Middle East and Africa trough Belarus, resulting in an unforeseen influx of migrants on the borders of the European Union and its Member States, namely Latvia, Lithuania, and Poland. To safeguard their national security security as well as the European Union, these countries have changed their border management and implemented new legislation to counter the political coercion exerted by Belarus. Nevertheless, the implementation of new legislation and procedures at the border has raised concerns regarding the extent to which Latvia, Lithuania, and Poland are upholding the human rights of these migrants. Hence, the thesis explores the crisis by examining the compliance of Latvia and Poland to the human rights obligations they have agreed to uphold. Additionally, it assesses whether the European Union, namely its institutions and officials, has effectively tackled the crisis in relation to human rights.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; European Convention on Human Rights; Migration; Belarus